2005
DOI: 10.1038/labinvest.3700345
|View full text |Cite
|
Sign up to set email alerts
|

Role of the integrin-linked kinase/PINCH1/alpha-parvin complex in cardiac myocyte hypertrophy

Abstract: Outside-in signaling from fibronectin (FN) through integrin receptors has been shown to play an important role in promoting cardiac myocyte hypertrophy and synergizes with other hypertrophic stimuli such as the alphaadrenergic agonist phenylephrine (PE) and mechanical strain. The integrin-linked kinase (ILK) is a critical molecule involved in cell adhesion, motility and survival in nonmyocytes such as fibroblasts and epithelial cells. Its role in cardiac myocytes is unclear. In this study, we demonstrate that … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

4
46
0
2

Year Published

2011
2011
2020
2020

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 58 publications
(52 citation statements)
references
References 39 publications
4
46
0
2
Order By: Relevance
“…We found that silencing the NHE1 gene significantly decreased the hypoxia-increased size of human PASMCs. In addition to cell size, cell volume, established by calculating the protein/DNA ratio, was used for the analysis of cell hypertrophy (39), because research indicates that the stimulation of protein synthesis without DNA replication is a feature of hypertrophy (33). We found that silencing NHE1 significantly decreased the protein/DNA ratio in human PASMCs cultured under hypoxia.…”
Section: Discussionmentioning
confidence: 96%
See 1 more Smart Citation
“…We found that silencing the NHE1 gene significantly decreased the hypoxia-increased size of human PASMCs. In addition to cell size, cell volume, established by calculating the protein/DNA ratio, was used for the analysis of cell hypertrophy (39), because research indicates that the stimulation of protein synthesis without DNA replication is a feature of hypertrophy (33). We found that silencing NHE1 significantly decreased the protein/DNA ratio in human PASMCs cultured under hypoxia.…”
Section: Discussionmentioning
confidence: 96%
“…For the analysis of protein/DNA ratios, PASMCs were plated in six-well plates. After the transfection of NHE1 siRNA and exposure to hypoxia, PASMCs were harvested, and the protein/DNA ratio was determined by measuring total DNA content and total protein content (33,34).…”
Section: Measurement Of Cell Hypertrophymentioning
confidence: 99%
“…16 ILK is upstream to a wide range of protein kinases involved in cell growth and cardiac hypertrophy, including protein kinase B, glycogen synthase kinase-3-β, extracellular signal-related kinase, and mammalian target of rapamycin 2 and ILK deletion causes severe cardiomyocyte apoptosis. 17 ILK is upregulated in human cardiac hypertrophy caused by left ventricular outflow obstruction, along with a wide range of hypertrophic genes. 4 ILK gene transfer improves cardiac function in post-MI and doxorubicin-induced cardiomyopathies.…”
Section: Functional Importance Of Ilkmentioning
confidence: 99%
“…Many of the currently known ILK-mediated functions require additional cofactors and interacting proteins. Increasing focus has therefore been put on the roles of the ternary complex comprising the proteins ILK, ␣-, ␤-, or ␥-parvin, and PINCH, PINCH1 or PINCH2 (5,26,30,34).…”
mentioning
confidence: 99%
“…Many of the currently known ILK-mediated functions require additional cofactors and interacting proteins. Increasing focus has therefore been put on the roles of the ternary complex comprising the proteins ILK, ␣-, ␤-, or ␥-parvin, and PINCH, PINCH1 or PINCH2 (5,26,30,34).The ILK-parvin-PINCH (IPP) complex provides physical linkage between integrin transmembrane receptors and the actin cytoskeleton and serves as a signaling mediator that transduces mechanical signals to downstream effectors (32). PINCH and parvins do not have catalytic activity but rather function as adapters for other signaling molecules such as Nck-2 and Ras suppressor 1 (RSU-1), through which PINCH can regulate c-Jun N-terminal kinase (JNK) (7,25).…”
mentioning
confidence: 99%